PERAN KOMITMEN PADA PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KINERJA PENGAJAR PONDOK PESANTREN KABUPATEN LAMONGAN - Ari Prasetyo (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The purpose of this study was to examine in depth the performance of teachers of Lamongan Regency Islamic Boarding School by looking at influencing factors, namely employee engagement and commitment as mediation. The design used in this research is quantitative. The population in this study was the teaching staff of Islamic boarding schools in Lamongan, East Java, with a sample size of 50 respondents. The independent variable used in the results of this study is given the notation X, namely: Employee engagement (X). The intervening variable is organizational commitment (Z). Dependent variable employee performance (Y). The data collection technique used in this research is a survey using a questionnaire. The analysis technique used in this research is Structural Equation Modeling with the Smart PLS (Partial Least Square) program. The research results show that organizational commitment mediates the influence of employee engagement on employee performance. Meanwhile, the direct influence of employee engagement on employee performance has been proven to be true.